A new conception of visual aesthetic sensitivity. (6th October 2019) - Corradi, Guido; Chuquichambi, Erick G.; Barrada, Juan Ramón; Clemente, Ana; Nadal, Marcos
Abstract : Aesthetic sensitivity has been defined as the ability to recognize and appreciate beauty and compositional excellence, and to judge artistic merit according to standards of aesthetic value. The Visual Aesthetic Sensitivity Test (VAST) has often been used to assess this ability, but recent research has revealed it has several psychometric problems. Such problems are not easily remedied, because they reflect flawed assumptions inherent to the concept of aesthetic sensitivity as traditionally understood, and to the VAST itself. We introduce a new conception of aesthetic sensitivity defined as the extent to which someone's aesthetic valuation is influenced by a given feature. Experiment 1 aimed to characterize aesthetic sensitivity to four prominent features in visual aesthetics: complexity, symmetry, contour, and balance. Experiment 2 aimed to replicate the findings of Experiment 1 and to assess the test–retest reliability of an instrument designed to measure aesthetic sensitivity to these features using an abridged set of stimuli. Our results reveal that people differ remarkably in the extent to which visual features influence their liking, highlighting the crucial role of individual variation when modelling aesthetic preferences. We did not find clear relations between the four measures of aesthetic sensitivity and personality, intelligence, and art interest and knowledge. Finally, our measurement instrument exhibited an adequate‐to‐good test–retest reliability.